2016
DOI: 10.1177/1359105315595117
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies and health-related quality of life after stroke

Abstract: Cerebral stroke causes a significant worsening of health-related quality of life. This review was conducted on studies investigating whether the levels of quality of life were influenced by the coping strategies used by stroke patients. We searched on PubMed and Web of Science databases and screening references of included studies and review articles for additional citations. From initial 389 publications, we included only 6 studies that met search criteria and described the association between coping and qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 51 publications
6
68
0
10
Order By: Relevance
“…This result could reflect a dysfunctional emotional regulation strategy, leading to reduce the use of emotion‐oriented coping in stressful situations when people are aimed at managing negative emotions associated with severe health problems such as heart diseases. Accordingly, emotion‐oriented coping has been associated with cardiac disorders in other studies (Bahremand, Alikhani, Zakiei, Janjani, & Aghaei, ; Lo Buono, Corallo, Bramanti, & Marino, ). Another likely explanation for this finding might be that a cardiac event, in some severe cases, could have reinforced avoidance of emotional processing.…”
Section: Discussionmentioning
confidence: 74%
“…This result could reflect a dysfunctional emotional regulation strategy, leading to reduce the use of emotion‐oriented coping in stressful situations when people are aimed at managing negative emotions associated with severe health problems such as heart diseases. Accordingly, emotion‐oriented coping has been associated with cardiac disorders in other studies (Bahremand, Alikhani, Zakiei, Janjani, & Aghaei, ; Lo Buono, Corallo, Bramanti, & Marino, ). Another likely explanation for this finding might be that a cardiac event, in some severe cases, could have reinforced avoidance of emotional processing.…”
Section: Discussionmentioning
confidence: 74%
“…2,3 İnme sonrası kas-iskelet-motor bozukluklar, duyusal sorunlar, bilişsel bozukluklar, dil-iletişim bozuklukları, gastrointestinal ve psikososyal sorunlar görülebilmekte; bu kısıtlılıklar bireyin aile, sosyal ve iş yaşamını olumsuz etkileyerek; bireyin yaşam kalitesinin azalmasına neden olmaktadır. 1,4,5 Yaşam kalitesi bireyin fiziksel sağlığı, psikolojik durumu, bağımsızlık düzeyi, sosyal ilişkileri ve çevresiyle olan etkileşimiyle bağlantılı olan bir kavramdır. 4 Bu kavram sağlık profesyonellerine bireyin hastalık ve iyileşme sürecinde yaşadığı fizyolojik problemler, bağımlılık, fonksiyon kayıpları ya da aile, sosyal ve iş yaşamında meydana gelen problemler hakkında veri sağlar; bu problemlerin çözümü konusunda sağlık profesyonellerine tıbbı tedavi ve hemşirelik bakımını planlamalarında rehberlik eder.…”
Section: Introductionunclassified
“…Prior studies have highlighted the despair and disappointment felt by stroke survivors after discharge from the hospital due to limited information given and encouragement by health professionals [12][13][14][15]. Other studies have found that individuals developed and used a range of coping strategies to adjust to life with stroke [16,17].…”
Section: Introductionmentioning
confidence: 99%